Testing and Determining the Form of Market Efficiency in Dhaka Stock Exchange (DSE) - Yasmin, Farhana (International Journal of Accounting and Financial Reporting, 2022)
This paper is focused on the idea of whether Dhaka Stock Market (DSM) is efficient in weak-form of Efficient Market Hypothesis (EMH) or not. As any country’s economic condition can be indicated by the efficiency of its stock market, so determining and measuring the different forms of efficiency has always been a well explored topic for researchers. In this paper, attempts have been made to determine and test the market efficiency and randomness of Dhaka Stock Exchange (DSE) in weak form. The entire Dhaka stock exchange has been evaluated by employing daily return from the two indices- DS30 and DSEX. Employing the normality test it is found that both the return series are not normally distributed. Moreover few parametric tests named Augmented Dickey-Fuller test (ADF), Autocorrelation Function (ACF), and Variance Ratio test (Lo & MacKinlay) have been done to examine the historic price dependencies or to examine the random walk hypothesis. The entire test results suggested that DSE is not efficient in weak form which means return from DSE does not follow a random walk.